1996
DOI: 10.1002/(sici)1097-0142(19961001)78:7<1587::aid-cncr38>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

The cost of conducting face-to-face household interviews in a rural, Native American population: The North Carolina Native American Cervical Cancer Prevention Project

Abstract: BACKGROUND. This article focuses on planning, developing, implementing, and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…Blinson et al (1996) identified potential difficulties with collecting information from American Indian women that might be applied to interviewing any individuals:…”
Section: Resultsmentioning
confidence: 99%
“…Blinson et al (1996) identified potential difficulties with collecting information from American Indian women that might be applied to interviewing any individuals:…”
Section: Resultsmentioning
confidence: 99%
“…Including open-ended questions is advised to allow for a story-telling approach to interviewing, which aligns with the communication style of Native communities (Fisher & Ball, 2005; Macedo et al, 2004; Strickland, 1999). Some authors specify a face-to-face semi-structured interview as the mode of choice for AI/AN populations (Blinson, Dignan, Michielutte, & Wells, 1996; Macedo et al, 2004; Pearson, Cheadle, Wagner, Tonsberg, & Psaty, 1994). Each tribe has its own distinct communication style, language and culture; however, the literature review identified cross-tribal commonalities which, when combined with reviews by those familiar with the customs of the tribes involved in this project, generated the foundation for the design of the survey.…”
Section: Methodsmentioning
confidence: 99%
“…Interviews were primarily conducted in person (85%), the preferred method for surveying in AI/AN communities (Blinson et al, 1996). Interviewers gave respondents the choice to complete the interview over the phone or in person.…”
Section: Methodsmentioning
confidence: 99%
“…Such nonparticipation is not only the result of lack of information; it is also due to cultural and gender-related factors. [13][14][15] Beyond the clinical, technical, financial, and organizational proficiency required of Papanicolaou test screening programs, essential elements are an awareness and understanding of cultural concepts of cancer and its prevention and sensitivity to cultural barriers.…”
Section: Discussionmentioning
confidence: 99%
“…In view of the potential partnership between public health and faith communities to reach underserved women, 15 we conducted a Maintaining Mammography Adherence Through Telephone Counseling in a Church-Based Trial…”
Section: Methodsmentioning
confidence: 99%